Predicting Marital Satisfaction Based on Sexual Satisfaction and Psychological Well-being in Married Women - Mohammadfarahmand, Gholamreza; Saboori Rad , Soma (Psychology of Woman Journal, 2023)
Objective: The present study aimed to predict marital satisfaction based on sexual satisfaction and psychological well-being in married women. Materials and Methods: The study was a descriptive and correlation type. The population of this research included all students of the Islamic Azad University, Qods City branch, in the academic year 2021-2022, from which 200 individuals were selected as the sample using a convenience sampling method. The main data for this research were obtained using the Marital Satisfaction Questionnaire by Natan et al. (1973), the Sexual Satisfaction Questionnaire by Yavari Kermani (2007), and the Psychological Well-being Questionnaire by Ryff and Keyes (1995). In the data analysis, descriptive statistics (central indicators, dispersion) and inferential statistics (multiple regression) were used. Findings: This study, by examining the relationship between variables, revealed that there is a positive and significant relationship between sexual satisfaction and marital satisfaction; and between psychological well-being and marital satisfaction. Furthermore, the results indicated that sexual satisfaction and psychological well-being have the predictive power for marital satisfaction in married women. Conclusion: Based on the findings, it can be concluded that sexual satisfaction and psychological well-being can predict marital satisfaction in women.